Chemoenzymatic Synthesis of Complex N‐Glycans of the Parasite S. mansoni to Examine the Importance of Epitope Presentation on DC‐SIGN recognition. (16th July 2021) - Srivastava, Apoorva D.; Unione, Luca; Bunyatov, Mehman; Gagarinov, Ivan A.; Delgado, Sandra; Abrescia, Nicola G. A.; Ardá, Ana; Boons, Geert‐Jan
Abstract: The importance of multivalency for N ‐glycan‐protein interactions has primarily been studied by attachment of minimal epitopes to artificial multivalent scaffold and not in the context of multi‐antennary glycans. N ‐glycans can be modified by bisecting GlcNAc, core xylosides and fucosides, and extended N ‐acetyl lactosamine moieties. The impact of such modifications on glycan recognition are also not well understood. We describe here a chemoenzymatic methodology that can provide N ‐glycans expressed by the parasitic worm S. mansoni having unique epitopes at each antenna and containing core xyloside. NMR, computational and electron microscopy were employed to investigate recognition of the glycans by the human lectin DC‐SIGN. It revealed that core xyloside does not influence terminal epitope recognition. The multi‐antennary glycans bound with higher affinity to DC‐SIGN compared to mono‐valent counterparts, which was attributed to proximity‐induced effective concentration. The multi‐antennary glycans cross‐linked DC‐SIGN into a dense network, which likely is relevant for antigen uptake and intracellular routing. Abstract : The molecular recognition of chemoenzymatically synthesized glycans derived from the parasitic worm S. mansoni by the human lectin DC‐SIGN was investigated by a combination of NMR, computational and electron microscopy. It uncovered the importance of glycan complexity for lectin recognition including the influence of glycan valency, core xylosylation and length of oligo‐LacNAc residues.